STRATEGI SEKOLAH INDONESIA RIYADH (SIR) DALAM MEMBANGUN BUDAYA ISLAMI SISWA DI LINGKUNGAN SEKOLAH - Saudin, Budi Marta; Wibisono, Hendar Ahmad (Pascasarjana Universitas Al-Qolam Malang, 2025)
This research aims to explain the strategies the Indonesian Embassy School of Riyadh (SIR) has carried out to develop Islamic culture among its students. The methodology used in this research is a descriptive qualitative method, employing research instruments such as observation, interviews, and documentation. As a school located abroad and within an Arab community, the Indonesian Embassy School of Riyadh (SIR) feels challenged to compete in quality with schools in Indonesia and Saudi Arabia. Various programs have been implemented, including instilling Islamic culture in students, hoping they will become more religious and improve their overall quality. The results of the research show that the school has instilled Islamic culture in its students through programs such as Qur'an recitations, dhuha prayer, dzuhur prayer in the congregation, morning prayers, prayers after dhuha prayers, prayers before and after studying, prayers after shalah dzuhur, darsul Qur'an, wearing Islamic clothing, practicing Islamic values (e.g., greetings, smiling, saying hello, eating with the right hand, eating while sitting, praying before eating), learning Arabic inside and outside the classroom, and participating in extracurricular activities. A new finding in this research is that living in an Arab country does not necessarily ensure that one can practice Islamic culture if they are not accustomed to it and regulated by a system. Many students cannot read the Qur'an well, so the school prepares pre-tahsin classes for them. Additionally, many students cannot speak Arabic according to correct Arabic language rules because they are accustomed to speaking Arabic with the amiyah dialect. The Indonesian Embassy School of Riyadh (SIR) has implemented various strategies intending to enable students to compete globally.